Sosialisasi dan Pelatihan Dasar-Dasar Keselamatan di Atas Kapal Kepada para Nelayan Desa Sapa Timur dan Relevansinya terhadap Keselamatan Pelayaran - Iksan Saifudin; Arika Palapa; Teriyanti Teriyanti; Haryadi Wijaya; Hendra Purnomo (Jurnal Pengabdian Masyarakat Waradin, 2024)
The Merchant Marine Polytechnic of Sulawesi Utara hold a community service to the people of Sapa Timur Village is motivated by the responsibility for implementing the Tri Dharma of Higher Education and the low level of public understanding of the basics of safety while on board ships. The activity was hold in May 7, 2024. The purpose of this community service is to achieve the target of the community service work program and increase public knowledge about basic safety and disaster preparedness training on ships. The method used is socialization and training. The results and conclusions obtained are majority of the community participants got many of understanding knowledge of the basics of safety on board and hoping for similar activities to be carried out again.